Digital transformation of waste banks through IoT-based polystyrene crusher innovation for strengthening the circular economy - Nalarsih, Retno Tri; Jayati, Ari Endang; Syahrial, Yoppi (Community Empowerment, 2025)
An increase in daily household waste volume to 771 kg in Tejorejo Village has disrupted irrigation functions and triggered flooding. This community service program aims to strengthen waste management and the local economy through the implementation of IoT-based Polystyrene Crusher technology. The methodology involved technical training, green economy management mentoring, and direct implementation of IoT-integrated recycling technology. Results demonstrated a significant increase in partner capacity in waste sorting (45%), equipment management (50%), and green marketing literacy (45%). The technology successfully shifted the business model from raw plastic sales to value-added processing, resulting in an initial gross income increase of 2.7%. The integration of IoT allows for precise monitoring of production efficiency while strengthening the resilience of community-based circular economies. This initiative proves that modernizing appropriate technology effectively mitigates environmental risks while creating sustainable economic opportunities at the rural level.